2021
DOI: 10.1111/ijcp.14104
|View full text |Cite
|
Sign up to set email alerts
|

The potential hepatoprotective effect of metformin in hepatitis C virus‐infected adolescent patients with beta thalassemia major: Randomised clinical trial

Abstract: Background Iron overload‐induced oxidative stress and transfusion‐acquired hepatitis C virus (HCV) infection are the main reasons of liver damage in beta thalassemia major (β‐TM). Objectives Based on metformin’s hepatic benefits in nondiabetic populations, the study aims to investigate the safety and the potential hepatoprotective effect of metformin in HCV‐infected β‐TM adolescent patients. Methods This was a prospective, randomised, parallel, controlled, open‐label study in which 60 HCV‐infected β‐TM adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Recently, it was reported that metformin was significantly associated with a decrease in mortality in obese or type 2 diabetic women hospitalized for COVID-19 [ 20 ]. As described above, several studies have reported that metformin can reduce the risk of infectious diseases and complications in DM patients, but studies on non-DM patients are insufficient [ [20] , [21] , [22] ]. In this study, the antiviral and immunomodulatory effects of metformin were investigated in non-DM conditions through in vitro and in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that metformin was significantly associated with a decrease in mortality in obese or type 2 diabetic women hospitalized for COVID-19 [ 20 ]. As described above, several studies have reported that metformin can reduce the risk of infectious diseases and complications in DM patients, but studies on non-DM patients are insufficient [ [20] , [21] , [22] ]. In this study, the antiviral and immunomodulatory effects of metformin were investigated in non-DM conditions through in vitro and in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions, lactate is metabolized in the liver and kidney after it is produced in the peripheral tissues. If HCV infection occurs, it mainly influences the mitochondrial respiratory chain complex genes, which leads to the activation of anaerobic processes and lactate and ROS accumulation [4,32]. This virus causes the destruction of the hepatocyte through multiple mechanisms, mainly by counteracting the activity of cellular defense factors.…”
Section: Hepatitis C Virus and Oxidative Stressmentioning
confidence: 99%
“…In hepatitis C virus-infected adolescents with beta thalassemia major, Mona S Abdel et al [32] reported a significant decrease in aspartate aminotransferase (AST), as well as an improvement in total antioxidant capacity and serum levels of malondialdehyde in the group treated with metformin, but without significant clinical improvement in the patients' condition.…”
Section: Hepatitis C Virus and Oxidative Stressmentioning
confidence: 99%